Application of Static Correction Technique on 2D Land Seismic Data in the South of Iraq - Ali, Hassan Zaid (Iraqi Journal of Science, 2019)
In our research, several different Statics solutions have been implemented in the processing of seismic data in the south of Iraq for (2D) line seismic survey (AK18) of Abu-khama project with length 32.4 Km and their corresponding results have been compared in order to find optimum static solutions. The static solutions based on the tomographic-principle or combining the low frequency components of field statics with high frequency ones of refraction statics can provide a reasonable static solution for seismic data in the south of Iraq. The quality of data was bad and unclear in the seismic signal, but after applying field statics there is an enhancement of data quality. The Residual static correction improved the qualities of seismic data, especially in the shallow part of the seismic section where makes the reflectors flatting, then these data became ready for interpretation, especially after applying of